Systematic Review: The Effect of Neiguan Acupressure Technique on Nausea and Vomiting in Postoperative Sectio Caesarea Patients with Spinal Anesthesia - Maghfiroh, Halima Aulia Ita; Ismail, Aem (Jurnal Sehat Indonesia (JUSINDO), 2025)
Nausea and vomiting after cesarean section with spinal anesthesia is a common problem that can interfere with patient recovery. The use of the Antigua acupressure technique (P6) as a non-pharmacological therapy shows the potential to reduce these symptoms. This study aims to analyze the effect of the neiguan acupressure technique on nausea and vomiting in postoperative sectio caesarea patients with spinal anesthesia. The method used was a systematic review by analyzing three relevant primary studies from PubMed and Google Scholar databases during the period 2019-2024. Data were collected and evaluated to assess the effectiveness of acupressure in relieving nausea and vomiting. The results showed that the neiguan acupressure technique significantly reduced nausea and vomiting, with measurements taken at hour 6 postoperatively showing p=0.003 and hour 12 p=0.005. All studies analyzed showed positive results regarding the effect of acupressure. The Neiguan acupressure technique is effective in overcoming nausea and vomiting in postoperative cesarean section patients with spinal anesthesia. However, other factors also contribute to changes in nausea and vomiting response, so this technique should be considered as part of a comprehensive therapeutic approach.